The Priority Tropical Diseases and Their Risk Factors in Coastal Areas of Southeast Sulawesi, Indonesia - Irma, Irma; Harleli, Harleli; Masluhiya AF, Swaidatul (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Tropical disease is a disease that must get serious attention because the incidence of this disease is getting higher, and the area of distribution is more expansive. Several tropical diseases with high morbidity rates, especially in developing countries and regions with tropical and subtropical climates, include diarrhea, pneumonia, upper respiratory tract infections (URTIs), tuberculosis (TB), and other diseasesThis study aims to identify the direct infectious tropical diseases and their priority determinants in Southeast Sulawesi Province Indonesia. This study is a descriptive study that aims to collect data and information related to the presence of priority tropical diseases in Southeast Sulawesi Province Indonesia. Research data was obtained from the Health Profile of Southeast Sulawesi Province, Indonesia in 2020. This study is a descriptive study that aims to collect data and information related to the presence of priority tropical diseases in Southeast Sulawesi Province Indonesia. The primary sources of this research data are books: Health Profile of the Republic of Indonesia, Indonesian Basic Health Research Results Report, and Southeast Sulawesi Provincial Health Office Profile 2019, as well as several relevant journals. Priority tropical diseases that occur in Southeast Sulawesi Province include URTIs (prevalence 2.77%), diarrhea (prevalence 5.5%), pneumonia (1.59% prevalence), tuberculosis (1.59% prevalence), and hepatitis (prevalence 0.66%). The determinants of the five priority tropical diseases found included environmental, behavioral, and socioeconomic factors. Priority tropical diseases in Coastal Area Southeast Sulawesi Indonesia are direct-communicable diseases, namely URTIs, diarrhea, pneumonia, TB, and hepatitis, with environmental, behavioral, and socioeconomic factors as determinants. Further research is needed regarding the main determinants of tropical diseases in Southeast Sulawesi